Knowledge of people with visual impairment about contraceptives: an exploratory study - Dunja Stekić Djindjić; Branka Jablan; Vesna Vučinić; Ivana Obrenović Ilić; Valentina Martać (Universa Medicina, 2026)
BackgroundKnowledge and information about contraceptives are key factors for the protection of reproductive health. Evidence from various parts of the world reveal that women with disabilities are facing widespread barriers in accessing public services. The aim of the study was to determine the knowledge of visually impaired people about contraceptives in relation to gender and level of education. MethodsA cross-sectional study involving 32 visually impaired people of whom 12 (37.5 %) were male and 20 (62.5%) were female between the ages of 20 and 30 years. Part of the Illustrative Questionnaire for Interviews - Surveys with Young People was used to assess knowledge about contraceptives. Chi-square tests were used to analyse the data. ResultsRespondents with visual impairment were familiar with contraceptives. They believe that condoms and birth control pills are the most effective means of protection against unintended pregnancy. With regard to the perception of the effectiveness of contraceptives, there are statistically significant differences by gender (p=0.011) only for abstinence as an effective contraceptive. Differences by level of education were found in the responses to the two statements "The condom is an effective means of contraception" (p=0.022) and "Condoms are only used in casual relationships, not in long-term relationships and marriage" (p=0.048). ConclusionAlthough the visually impaired respondents showed that they have some knowledge about contraceptives, it is necessary to consistently organize additional education and provide information about reproductive health in an accessible form.